2014
DOI: 10.1530/erc-14-0248
|View full text |Cite
|
Sign up to set email alerts
|

Bringing androgens up a NOTCH in breast cancer

Abstract: While it has been known for decades that androgen hormones influence normal breast development and breast carcinogenesis, the underlying mechanisms have only been recently elucidated. To date, most studies have focused on androgen action in breast cancer cell lines, yet these studies represent artificial systems that often do not faithfully replicate/ recapitulate the cellular, molecular and hormonal environments of breast tumours in vivo. It is critical to have a better understanding of how androgens act in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 192 publications
(164 reference statements)
1
20
0
Order By: Relevance
“…In contrast, a similar study in normal human breast tissues by Wang et al (2014) found that >90 % of ERα MECs also expressed AR, as determined by dual immunohistochemistry [86]. The latter finding is consistent with the observation that AR positivity is much higher (20-80 %) than ERα positivity (0-20 %) in normal breast tissues (reviewed in [74,87]). Aside from technical sources of variation, likely reasons for such discrepancy between these studies include the age and reproductive status of women at the time of tissue harvest.…”
Section: Androgenssupporting
confidence: 60%
“…In contrast, a similar study in normal human breast tissues by Wang et al (2014) found that >90 % of ERα MECs also expressed AR, as determined by dual immunohistochemistry [86]. The latter finding is consistent with the observation that AR positivity is much higher (20-80 %) than ERα positivity (0-20 %) in normal breast tissues (reviewed in [74,87]). Aside from technical sources of variation, likely reasons for such discrepancy between these studies include the age and reproductive status of women at the time of tissue harvest.…”
Section: Androgenssupporting
confidence: 60%
“…In primates, AR is expressed in all stages of mammary development except for late pregnancy and lactation and appears to show small, non-significant variation across the menstrual cycle (Cheng et al 2005). Ar knockout transgenic models generally indicate that AR is required for normal mammary gland development (reviewed by Hickey et al (2012), Chang et al (2013) and Tarulli et al (2014)). In the human, AR appears to have a protective role in normal breast at least in part by opposing ERa action (Dimitrakakis et al 2003, Eigeliene et al 2012, Ochnik et al 2014.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…AR binds to specific DNA sequences called androgen response elements (AREs) within the promoter/enhancer regions and regulate target gene transcription by recruiting coactivators or corepressors. Androgens can cross-talk with multiple signal transduction pathways, including phosphatidylinositol 3-kinase(PI3K)/Akt pathway (Lee et al 2015), Wnt/β-catenin signaling pathway (Song and Gelmann 2005), growth hormone (GH)/Insulin-like growth factor I (IGF-I) axis (Wu et al 2006;Zhu and Kyprianou 2008), and Notch signaling (Dubois et al 2012;Tarulli et al 2014). …”
Section: Introductionmentioning
confidence: 99%